(Table 1) Age determination of stalagmites of the Marcello Arévalo Cave in Chile, supplementary data to: Schimpf, Daniel; Kilian, Rolf; Kronz, Andreas; Simon, Klaus; Spötl, Christoph; Wörner, Gerhard; Deininger, Michael; Mangini, Augusto (2011): The significance of chemical, isotopic, and detrital components in three coeval stalagmites from the superhumid southernmost Andes (53°S) as high-resolution palaeo-climate proxies. Quaternary Science Reviews, 30(3-4), 443-459 - Schimpf, Daniel; Kilian, Rolf; Kronz, Andreas (PANGAEA - Data Publisher for Earth & Environmental Science, 2011)
Stalagmites are important palaeo-climatic archives since their chemical and isotopic signatures have the potential to record high-resolution changes in temperature and precipitation over thousands of years. We present three U/Th-dated records of stalagmites (MA1-MA3) in the superhumid southern Andes, Chile (53°S). They grew simultaneously during the last five thousand years (ka BP) in a cave that developed in schist and granodiorite. Major and trace elements as well as the C and O isotope compositions of the stalagmites were analysed at high spatial and temporal resolution as proxies for palaeo-temperature and palaeo-precipitation. Calibrations are based on data from five years of monitoring the climate and hydrology inside and outside the cave and on data from 100 years of regional weather station records. Water-insoluble elements such as Y and HREE in the stalagmites indicate the amount of incorporated siliciclastic detritus. Monitoring shows that the quantity of detritus is controlled by the drip water rate once a threshold level has been exceeded. In general, drip rate variations of the stalagmites depend on the amount of rainfall. However, different drip-water pathways above each drip location gave rise to individual drip rate levels. Only one of the three stalagmites (MA1) had sufficiently high drip rates to record detrital proxies over its complete length. Carbonate-compatible element contents (e.g. U, Sr, Mg), which were measured up to sub-annual resolution, document changes in meteoric precipitation and related drip-water dilution. In addition, these soluble elements are controlled by leaching during weathering of the host rock and soils depending on the pH of acidic pore waters in the peaty soils of the cave's catchment area. In general, higher rainfall resulted in a lower concentration of these elements and vice versa. The Mg/Ca record of stalagmite MA1 was calibrated against meteoric precipitation records for the last 100 years from two regional weather stations. Carbonate-compatible soluble elements show similar patterns in the three stalagmites with generally high values when drip rates and detrital tracers were low and vice versa. d13C and d18O values are highly correlated in each stalagmite suggesting a predominantly drip rate dependent kinetic control by evaporation and/or outgassing. Only C and O isotopes from stalagmite MA1 that received the highest drip rates show a good correlation between detrital proxy elements and carbonate-compatible elements. A temperature-related change in rainwater isotope values modified the MA1 record during the Little Ice Age (~0.7-0.1 ka BP) that was ~1.5 °C colder than today. The isotopic composition of the stalagmites MA2 and MA3 that formed at lower drip rates shows a poor correlation with stalagmite MA1 and all other chemical proxies of MA1. 'Hendy tests' indicate that the degassing-controlled isotope fractionation of MA2 and MA3 had already started at the cave roof, especially when drip rates were low. Changing pathways and residence times of the seepage water caused a non-climatically controlled isotope fractionation, which may be generally important in ventilated caves during phases of low drip rates. Our proxies indicate that the Neoglacial cold phases from ~3.5 to 2.5 and from ~0.7 to 0.1 ka BP were characterised by 30% lower precipitation compared with the Medieval Warm Period from 1.2 to 0.8 ka BP, which was extremely humid in this region.
This dataset is supplement to doi:10.1016/j.quascirev.2010.12.006
Keywords: Datensammlung